Grisel’s Syndrome in Children: Two Case Reports and Systematic Review of the Literature - Nicole Pini; Martina Ceccoli; Patrizia Bergonzini; Lorenzo Iughetti (Case Reports in Pediatrics)
Background and Objective. Grisel’s syndrome is a rare syndrome characterized by nontraumatic rotatory subluxation of the atlantoaxial joint. It usually affects children and typically presents with torticollis after ear, nose, and throat (ENT) surgery or head and neck infections. In the pediatric literature, there is only a small amount of available data; moreover, no systematic review has been previously done with focus on the pediatric population. We report our experience of two cases, and we provide a systematic review on Grisel’s syndrome in children in order to offer a deeper insight about its clinical presentation, its current diagnosis, and principles of treatment. Case Reports and Review. We describe two boys of 9 and 8 years old, who developed atlantoaxial subluxation after adenoidectomy. Considering the early diagnosis, a conservative treatment was chosen, with no recurrence and no sequelae at follow-up. We identified 114 case reports, of which 90 describe children, for a total of 171 pediatric patients. Of the 154 cases in which cause was reported, 59.7% presented a head and neck infection and 35.7% had previous head and neck surgery. There is no sex prevalence (49.7% males versus 50.2% females). Mean delay in diagnosis is 33 days. Eight % of the patients had neurological impairment of the 165 cases which mentioned treatment, 96% underwent a conservative treatment, of whom the 8.8% recurred with the need of surgery. As a whole, 12% underwent surgery as a first- or second-line treatment. 3 6% of the patients whose follow-up was reported developed a sequela, minor limitation of neck movement being the most frequent. Conclusion. Grisel’s syndrome should be suspected in children with painful unresponsive torticollis following ENT procedures or head and neck inflammation. CT scan with 3D reconstruction is the gold standard for diagnosis, allowing the identification of the subluxation and the classification according to the Fielding–Hawkins grading system. Surgical treatment is indicated in case of high-grade instability or failure of conservative treatment. Review of the literature shows how early diagnosis based on clinical and radiological evaluation is crucial in order to avoid surgical treatment and neurologic sequelae.